Primary Central Nervous System Angiitis Mimicking a Space-Occupying Lesion - Gandham, Edmond Jonathan; Patel, Bimal; Mathew, Vivek; Raju, Krishna Prabhu (Indian Journal of Neurosurgery, 2022)
Background and Purpose Intracranial space-occupying lesions are a sine qua non for neoplastic lesions; however, occasionally non-neoplastic lesions mimic neoplastic lesions, leading to diagnostic dilemmas. We report our experience with three patients who presented with a progressive hemispheric syndrome and the diagnostic considerations involved in the cases.Materials and Methods In this retrospective study, we included three patients with primary angiitis of central nervous system (PACNS) who underwent craniotomy and biopsy, suspecting it to be mass lesions. Demographic features, clinical features, radiological features, histopathology, treatment, and clinical outcomes were studied.Results Majority were males. The male:female ratio was 2:1. Lobar involvement was common. MR brain with contrast showed features of high-grade glioma. Despite hemispheric involvement, there was no mass effect. Perilesional edema was seen in all cases. All underwent craniotomy and biopsy; histopathology was consistent with PACNS. All patients were treated with corticosteroids and cyclophosphamide. Rituximab was used in addition to cyclophosphamide in one patient. At 2 years follow-up, two patients were in disease remission and one patient died due to disease progression.Conclusion PACNS has a protean clinical manifestation. A high index of suspicion is required in cases with atypical clinical presentations, radiological features, and normal angiograms. Early histological diagnosis and aggressive immunotherapy with high-dose corticosteroids combined with intravenous cyclophosphamide yields favorable outcomes.
Keywords: primary CNS angiitis; craniotomy; corticosteroids; cyclophosphamide